2015
DOI: 10.3174/ajnr.a4569
|View full text |Cite
|
Sign up to set email alerts
|

Giant Intracranial Aneurysms at 7T MRI

Abstract: SUMMARY: Giant intracranial aneurysms are rare vascular pathologies associated with high morbidity and mortality. The purpose of this in vivo study was to assess giant intracranial aneurysms and their wall microstructure by 7T MR imaging, previously only visualized in histopathologic examinations. Seven giant intracranial aneurysms were evaluated, and 2 aneurysms were available for histopathologic examination. Six of 7 (85.7%) showed intraluminal thrombus of various sizes. Aneurysm walls were depicted as hypoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Ultra-high field (UHF) MRI at 7 Telsa (T) has demonstrated strong clinical benefits in neuroimaging (1,2), for example, for the diagnosis of tumorous entities (3,4) or the assessment of patients with multiple sclerosis (5,6). UHF MR angiography (MRA) also showed strong improvements in comparison to clinical field strengths at 1.5 or 3T (7)(8)(9), and the increased resolution enables the depiction of very small blood vessels (lenticulostriate arteries (10,11), perforating arteries (12), subcallosal artery (13)), as well as small aneurysms (14)(15)(16)(17)(18)(19)(20)(21) that may cause a subarachnoid hemorrhage. Nowadays, the gold standard for depiction of small aneurysms is invasive digital subtraction angiography.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-high field (UHF) MRI at 7 Telsa (T) has demonstrated strong clinical benefits in neuroimaging (1,2), for example, for the diagnosis of tumorous entities (3,4) or the assessment of patients with multiple sclerosis (5,6). UHF MR angiography (MRA) also showed strong improvements in comparison to clinical field strengths at 1.5 or 3T (7)(8)(9), and the increased resolution enables the depiction of very small blood vessels (lenticulostriate arteries (10,11), perforating arteries (12), subcallosal artery (13)), as well as small aneurysms (14)(15)(16)(17)(18)(19)(20)(21) that may cause a subarachnoid hemorrhage. Nowadays, the gold standard for depiction of small aneurysms is invasive digital subtraction angiography.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, histopathological analysis of two specimens revealed a homogeneous deposition of iron within the adventitia and smooth muscle layers. 40 Because of a strong blooming effect in SWI at ultra-high magnetic field strengths, aneurysm wall thickness was overestimated approximately 1.5-fold compared with TOF-MRA, which showed excellent correlation with histopathological measurements. Blankena and colleagues used 7T magnetization-prepared inversion-recovery turbo spin-echo (MPIR-TSE) sequences to correlate wall thickness and wall shear stress in 11 UIAs.…”
Section: -Tesla Mri Of Brain Aneurysmsmentioning
confidence: 85%
“…16,17,37 Recent studies using ultra-high-field 7T MRA have enhanced the diagnostic accuracy of this neurovascular imaging technique to delineate microvascular structures and even vessel walls. [20][21][22][23] The presented study used dedicated MRA sequences to identify possible collateral networks with up to 2.4-to 3.2-fold higher resolution than in recently reported studies on MMA using 7T MRA. 17,37 This study shows the possible clinical application of 7T MRA to identify submillimeter collateral networks in MMA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested the feasibility and diagnostic accuracy for delineation of submillimeter perforating arteries, microvascular structures, and vessel walls. [20][21][22][23][24][25][26] Therefore, studies on collateral networks in MMA using ultra-high-field 7T MR imaging are warranted. Better visualization of deeply seated collateral networks (DSCNs) in MMA might improve our understanding of this rare and complicated pathophysiology and presumably facilitate treatment decisions.…”
mentioning
confidence: 99%